PRICING AND COSTING PRACTICES IN TELECOMMUNICATIONS: THE BRAZILIAN EXPERIENCE AND CHALLENGES - Franklin Jr., Sergio Luis; Pizzolato, Nelio Domingues (Brazilian Journal of Operations & Production Management, 2013)
In this paper we provide an overview of the Brazilian regulatory framework for telecommunications, emphasizing the policies and models adopted for setting interconnection and access prices. In particular, we show how the regulations on interconnection and access services have evolved over time since the liberalization of the telecommunications sector (from July 1997 to December 2012), describe the two costing methodologies adopted, and formulate alternative approaches to address the regulatory challenges associated with the pricing/costing mechanism used, the target balance between service-based and facilities-based competition, and the impact of real options on the cost-based prices of regulated telecommunications services.